Genome-wide scan for signatures of selection in Hanwoo and Angus cattle using whole-genome sequence data - Hyoun Ju Kim; Nasir Moghaddar; Sam Clark; Julius H. J. van der Werf; Sara de las Heras-Saldana (PLoS ONE, 2025)
This study used whole-genome sequence data on 406 beef cattle (203 Hanwoo and 203 Angus) to detect signatures of selection using four different methods; integrated haplotype score (iHS), Rsb, XP-EHH, and runs of homozygosity (ROH). Based on Rsb and XP-EHH analysis, 36 and 21 genomic regions differed significantly between Angus and Hanwoo breeds. Within breeds, we identified 108 regions (76 in Hanwoo and 32 in Angus) with the ROH analysis and 331 regions with the iHS method (298 in Hanwoo and 33 in Angus). The candidate genes related to meat quality, such as HSPA9 and LPL, were found within Hanwoo, while genes associated with growth and meat quantity traits, including ACTC1 and TMEM68, were identified within Angus. This study can assist in understanding the selection history of these breeds and identifying the genomic regions associated with the traits selected for in the breeding programs for these cattle breeds.